THE EFFECT OF SOCIAL RESTRICTIONS ON THE PSYCHOLOGICAL SOCIAL INTERACTIONS OF ELEMENTARY SCHOOL CHILDREN IN THE SCHOOL ENVIRONMENT - Sheyla Aulia Sagita; Agis Nur Fazhan Sulistira; Wahyunengsih Wahyunengsih (ADIBA : JOURNAL OF EDUCATION, 2022)
This study aims to determine the effect of social restrictions on the psychological social interactions of elementary school children. The reason for taking this research is because the social restriction policy during the pandemic made school activities closed and replaced with learning at home and reduced children's social interaction. So it demands not to interact directly with his friends socially. They are used to learning happily at school, they can meet and interact directly with their friends, but with social restrictions during this pandemic, they cannot interact directly. The method used in this research is a qualitative research method. Qualitative research is research that explains a lot by using words rather than numbers. The type of research used is field research and interviews, this research was carried out systematically by interviewing teachers and parents of students and making observations to elementary schools. In this study, the researchers found that the social interaction of elementary school children decreased, they became quieter and rarely interacted due to the influence of social restrictions during the pandemic.